Annie Gray: Victory in the Kitchen. The Life of Churchill’s Cook - Jaine, Tom (Petits Propos Culinaires, 2020)
Annie Gray: Victory in the Kitchen. The Life of Churchill’s Cook: Profile Books, 2020: 392 pp., hardback, £16.99.